2013
DOI: 10.1200/jco.2012.44.6831
|View full text |Cite
|
Sign up to set email alerts
|

Statins and the Risk of Hepatocellular Carcinoma in Patients With Hepatitis C Virus Infection

Abstract: Among patients with HCV infection, statin use was associated with reduced risk of HCC. Further research is needed to elucidate the mechanism responsible for this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
185
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(196 citation statements)
references
References 39 publications
(15 reference statements)
11
185
0
Order By: Relevance
“…Considerably longer follow-up will also be required to assess any benefit of statins on the long-term sequelae of NAFLD, i.e., cirrhosis and hepatocellular cancer (HCC). Notably, observational studies reported a decreased risk of HCC in patients treated with statins regardless of the cause (NAFLD, hepatitis B or C) [37][38][39] . Indeed, in a recent metaanalysis of 10 studies (n = 1459417), statins reduced the risk for HCC by 37% [37] .…”
Section: Effects On Liver Histologymentioning
confidence: 99%
“…Considerably longer follow-up will also be required to assess any benefit of statins on the long-term sequelae of NAFLD, i.e., cirrhosis and hepatocellular cancer (HCC). Notably, observational studies reported a decreased risk of HCC in patients treated with statins regardless of the cause (NAFLD, hepatitis B or C) [37][38][39] . Indeed, in a recent metaanalysis of 10 studies (n = 1459417), statins reduced the risk for HCC by 37% [37] .…”
Section: Effects On Liver Histologymentioning
confidence: 99%
“…Accordingly, statins have been shown to improve the antiviral activity of HCV polymerase and protease inhibitors in vitro (7), and are associated with an enhanced virologic response to peginterferon and ribavirin therapy in humans (8). In line with these pleotropic effects, statins have been reported to decrease the risk of HCC (9,10). A clinical trial also found a 9-month improvement in survival among advanced HCC patients treated with pravastatin (11).…”
Section: Introductionmentioning
confidence: 70%
“…Their study also discovered that an accumulated dose of statins of <215.4 DDD reduced HCC risk by 38% among patients, compared with those who did not receive statins. They concluded that an accumulated dose of statins of >215.4 DDD was not associated with any significant differences, which they similarly attributed to an inadequate sample size [2][3][4]. However, it was determined in the present study that cumulative daily dose, cumulative days, and average daily dose were all linearly correlated (P<0.001) regarding the correlation between statin drug usage and HCC risk among the patients with DM and either hepatitis B or hepatitis C. One possible reason for this discrepancy, in comparison to the study by Chiu et al [1] did not focus solely on whether receiving statin drugs could reduce HCC risk among patients with DM.…”
Section: Discussionmentioning
confidence: 99%